Development of a psychological support system for skiers based on biopsychosocial factors - Zebzeev, V.V.; Sokolovskaia, S.V.; Fedoseev, A.M.; Finogenov, A.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop a model of psychological support for the training of ski jumpers based on biopsychosocial factors. Methods and structure of the study. To achieve the set goal, the following methods were used in the work: theoretical analysis of scientific and methodological literature and documents, questionnaires and modelling. Key biopsychosocial determinants of ski jumpers' performance were identified, including psychophysiological, cognitive, emotional, and social characteristics. The study was conducted at the Tchaikovsky State Physical Education and Sport Academy from 1 February to 1 October 2025. Results and conclusions. An innovative model of psychological support has been developed, which has a modular structure and includes four interrelated components: conceptual, diagnostic, content-forming, and control-correcting. The model provides systematic diagnosis of biological, psychological, and social factors, prevention of unfavourable pre-start conditions, and development of stress resistance, emotional regulation, and communication skills in athletes. The implementation of the proposed model contributes to a comprehensive improvement in the effectiveness of psychological training for ski jumpers, strengthening the interaction between the athlete, coach and sports psychologist, as well as increasing the stability of sports results in competitive conditions.